Pharmacodynamic effects of a new fixed-dose clopidogrel–aspirin combination compared with separate administration of clopidogrel and aspirin in patients treated with coronary stents: The ACCEL-COMBO trial. (17th February 2017) - Koh, Jin-Sin; Park, Yongwhi; Tantry, Udaya S.; Ahn, Jong-Hwa; Kang, Min Gyu; Kim, Kyehwan; Jang, Jeong Yoon; Park, Hyun Woong; Park, Jeong Rang; Hwang, Seok-Jae; Kwak, Choong Hwan; Hwang, Jin-Yong; et al.
Abstract: Dual antiplatelet therapy (DAPT) with clopidogrel and aspirin is a widely prescribed regimen to prevent ischemic events in patients undergoing percutaneous coronary intervention (PCI). A fixed-dose combination (FDC) capsule (HCP0911) has been developed to provide dosing convenience and improve adherence. We compared the antiplatelet effects of single daily dose HCP0911 with separate treatment with daily 75 mg clopidogrel plus 100 mg aspirin. This was a randomized, open-label, two-period, crossover, non-inferiority study conducted in stented patients who had been treated for at least 6 months with clopidogrel and aspirin. Thirty patients were randomly assigned to receive either daily 75 mg clopidogrel plus 100 mg aspirin treatment or HCP0911 for 2 weeks and then were crossed over to the other treatment for 2 weeks. Pharmacodynamic effects were measured with VerifyNow, light transmittance aggregometry (LTA), and thromboelastography (TEG ® ). The primary endpoint was P2Y12 Reaction Units (PRU) measured by VerifyNow. PRUs during treatment with HCP0911 were not inferior to those during separate treatment (202 ± 52 vs. 207 ± 60 PRU; mean difference, −5 PRU; 90% confidence interval of difference, −23 to 13 PRU; P for non-inferiority = 0.015 for predetermined limit). "BASE" and Aspirin Reaction Units by VerifyNow did not differ between the two treatments. During each treatment, there were no differences in maximal and final platelet aggregations by LTA (all P values ≥0.822) and TEG ® measurements. In conclusion, in stented patients, the antiplatelet effect of a fixed-dose clopidogrel–aspirin combination, HCP0911, was not inferior to separate administration of clopidogrel and aspirin.